The Past, Present, and Future of the Canadian Labour Movement: Interrogating Insider Accounts - Savage, Larry (Labour / Le Travail, 2020)
Review essay of "A Grander Vision: My Life in the Labour Movement" (2019) by Sid Ryan, and "A New Kind of Union: Unifor and the Birth of the Modern Canadian Union" (2019) by Fred Wilson.